2013
DOI: 10.1051/0004-6361/201321059
|View full text |Cite
|
Sign up to set email alerts
|

The variability of carbon stars in the Sagittarius dwarf spheroidal galaxy

Abstract: Context. Stars have been forming in massive dwarf spheroidal galaxies continuously for several Gyr. The detection of AGB carbon stars indicates that an intermediate-age population is present. Sagittarius, the most massive, contains some 100 carbon stars. Most of them are probably variable. Aims. Using photometric monitoring we intend to detect long period variables among Sagittarius carbon stars. We should be able to identify mira variables, semi-regular and irregular variables, and to determine their period a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
5
12
0
Order By: Relevance
“…Their presence, however, is a reminder of our poor understanding of the thermal pulsating AGB phase and the carbon-rich to oxygen-rich transition. Overall, the SagDIG proper-motion based carbon/oxygen ratio is consistently within the Battinelli & Demers (2013) reported error. Being the most metal-poor galaxy in the Battinelli & Demers (2013) sample, SagDIG plays an important role in establishing the zero point of the [Fe/H]-log (C/M0+) anti-correlation.…”
Section: Discussionsupporting
confidence: 78%
“…Their presence, however, is a reminder of our poor understanding of the thermal pulsating AGB phase and the carbon-rich to oxygen-rich transition. Overall, the SagDIG proper-motion based carbon/oxygen ratio is consistently within the Battinelli & Demers (2013) reported error. Being the most metal-poor galaxy in the Battinelli & Demers (2013) sample, SagDIG plays an important role in establishing the zero point of the [Fe/H]-log (C/M0+) anti-correlation.…”
Section: Discussionsupporting
confidence: 78%
“…Not all of the latter objects are spectroscopically confirmed C stars, but their near-infrared colours strongly favour this chemistry. One object of Battinelli & Demers (2013), called Sgr 13 (2MASS J185329.37−293824.1), is also in the list of Whitelock et al (1999), and the period determinations agree. In the end, 22 Miras and two SRs are known with periods available.…”
Section: Comparison With Sagittariusmentioning
confidence: 84%
“…Four C-rich Miras and one SR in Sgr have been reported by Whitelock et al (1999) with measured periods, and six other C Miras were found by Lagadec et al (2009). Recently, Battinelli & Demers (2013) identified and monitored 13 Miras and one SR in Sgr. Not all of the latter objects are spectroscopically confirmed C stars, but their near-infrared colours strongly favour this chemistry.…”
Section: Comparison With Sagittariusmentioning
confidence: 90%
See 1 more Smart Citation
“…We can check this relation using the sample of Battinelli & Demers (2013), who obtained J and K light curves for many of the Mauron group stars, and so overlap our first sample. We see that the fits are comparable, although both show some considerable scatter (Fig.…”
Section: Distance Determination and Uncertainties On Distancesmentioning
confidence: 99%